Health-Related Quality of Life in HIV-Infected Men Who Have Sex with Men in China: A Cross-Sectional Study - Song, Bo; Yan, Cunling; Lin, Yuanlong; Wang, Fuxiang; Wang, Limei (Medical science monitor, 2016)
BACKGROUND China is undergoing a rapid growth in the human immunodeficiency virus (HIV) epidemic involving men who have sex with men (MSM). Reports about their health-related quality of life (HRQOL) are scarce. This study aimed to assess the HRQOL and factors influencing HIV-positive MSM in a city in the northeast of China. MATERIAL AND METHODS A cross-sectional study was conducted in Harbin city (Heilongjiang, China). HIV-positive MSM (n=125) were interviewed using the WHOQOL-HIV-BRIEF scale, the Berger HIV Stigma Scale, and other HIV-related questionnaires from June to August 2013. RESULTS Among the 6 dimensions of the HRQOL, HIV-related stigma was negatively associated with psychological (r=-0.316, P=0.0003) and spirituality domains (r=-0.324, P=0.0002). Physician support was positively associated with independence domain (r=0.393, P<0.0001). Hostile mentality was associated with psychological (r=0.479, P<0.0001) and spirituality domains (r=0.431, P<0.0001). Adverse effects of HAART were significantly correlated with physical (r=-0.542, P<0.0001) and psychological (r=-0.554, P<0.0001) domains. Multiple logistic regression showed that stigma (odds ratio (OR)=1.251, 95% confidence interval (95%CI): 1.088-1.439, P=0.002) and adverse effects of HAART (OR=1.117, 95%CI: 1.069-1.167, P<0.0001) were independent risk factors for low HRQOL. Physician support (OR=0.961, 95%CI: 0.941-0.982, P=0.0002) and CD4+ counts >350 (OR=0.033, 95%CI: 0.005-0.208, P=0.001) were independent protective factors in MSM receiving HAART. Hostile mentality (OR=0.936, 95%CI: 0.906-0.967, P<0.0001) was an independent protective factor of HRQOL in MSM not receiving HAART. CONCLUSIONS Psychological factors such as HIV-related stigma, hostile mentality, and physician support have a significant effect on HRQOL in MSM. These findings suggest specific psychological interventions to improve HRQOL in HIV-positive MSM in China.